Cancer Treatment: Mutual Destruction of Deep Lung Tumor Tissues by Nanodrug‐Conjugated Stealth Mesenchymal Stem Cells (Adv. Sci. 5/2018) - Kim, Sang‐Woo (Adv Sci (Weinh), 2018)
In article https://doi.org/10.1002/advs.201700860, Sang‐Hyun Kim, Dongwoo Khang, and co‐workers demonstrate stealth mesenchymal stem cells armed with anti‐cancer nanodrug that successfully eradicate and are mutually destructive with malignant lung cancers. Using this method, the current clinical dose of anticancer drug for the treatment of lung cancer can be decreased by more than 100‐fold without triggering immunotoxicity. [Image: see text]